Effect of replacing alfalfa hay with Leucaena leucocephala (L. Leucocephala) leaves on in vitro gas production, digestibility and in situ degradability in buffalo - Tahereh Mohammadabadi; Morteza Chaji; Ehsan Direkvandi; Othman Alqaisi (Acta Scientiarum. Animal Sciences, 2021)
. This study was performed to investigate the effect of replacing alfalfa hay by L. leucocephala leaves in proportions of 25, 50 and 100% on in vitro gas production (GP) parameter, digestibility and in situ degradability in buffalo. Results showed that the volume of GP at 2 to 12 hours after incubation was significantly affected by replacing alfalfa hay with L. leucocephala leaves. In vitro digestibility of organic matter (OMD) differed significantly between treatment as it declined by increasing the alfalfa hay substitution rate from 25 to 100%. The microbial crude protein (MCP) differed significantly between treatments and was the greatest of 589 and 599 mg g-1 of dry matter (DM) when L. leucocephala leaves replaced alfalfa hay at 25 and 50%. The in vitro digestibility of DM (IVDMD) increased significantly at 50% L. leucocephala replacement rate. Moreover, substituting alfalfa hay by L. leucocephala had a significant effect on the in situ degradability parameters. The insoluble but potentially degradable fraction (B) and potential of degradability (A+B) significantly increased for treatment contain 50% L. leucocephala leaves. The effective degradability (ED) was significantly different between dietary treatments and was the greatest when alfalfa hay was replaced by 25 and 50% L. leucocephala. In conclusion, L. leucocephala leaves can substitute 25 to 50% of dietary alfalfa hay in buffalo rations without effect on rumen efficiency.